2014
DOI: 10.1159/000366351
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of miR-140 Induces EMT and Promotes Invasion by Targeting Slug in Esophageal Cancer

Abstract: Background/Aims: MicroRNAs (miRNAs) are reported to regulate cell invasion and functions by interfering with the translation of target mRNAs, but the role of miRNAs in esophageal cancer (EC) remains unclear. Methods: RT-PCR and Western blot were used to detect the expression of miRNAs and candidate genes in EC samples (n=89). miR-140 mimics and inhibitor were tansfected in human TE-1 and Eca-109 cells. The transwell assay was used to examine the cell invasive ability. The regulation mechanism was confirmed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 29 publications
6
41
0
Order By: Relevance
“…For instance, miR-1290 was significantly upregulated in ESCC tissue samples, and ectopic miR-1290 expression potently promoted ESCC cell growth, migration and invasion in vitro (25). miR-140 expression was decreased in the EC tissues and regulated the cell invasion of EC via controlling Slug expression (30). It has also been shown that miR-625 expression is lower in EC tissues than in the corresponding adjacent tissues and may regulate the proliferation and invasion of EC cells by targeting Sox2 (31).…”
Section: Discussionmentioning
confidence: 98%
“…For instance, miR-1290 was significantly upregulated in ESCC tissue samples, and ectopic miR-1290 expression potently promoted ESCC cell growth, migration and invasion in vitro (25). miR-140 expression was decreased in the EC tissues and regulated the cell invasion of EC via controlling Slug expression (30). It has also been shown that miR-625 expression is lower in EC tissues than in the corresponding adjacent tissues and may regulate the proliferation and invasion of EC cells by targeting Sox2 (31).…”
Section: Discussionmentioning
confidence: 98%
“…Transcription factor Snail suppresses E-cadherin effecting cell differentiation, and migratory and invasive properties, inducing cell movement and survival. It is already reported that miR-140 targeting Slug (Snail2) to regulate the invasion in EC [1]. GSK3β binds to and phosphorylates Snail, thereby regulating its function, and together these proteins act as a molecular switch for many signaling pathways [25].…”
Section: Psat1 Induces Cell Invasion In Escc Cell Linesmentioning
confidence: 99%
“…It is the eighth most common cancer globally and the sixth most common cause of cancerrelated death [1][2][3][4]. This type of cancer is about four times more common in men than in women and there are vastly different rates of occurrence between countries with China accounting for about half of all cases [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…PCR was performed under the following conditions: Denaturation at at 50˚C for 2 min, followed by 40 cycles of 95˚C for 15 sec and 60˚C for 1 min. Protein expression was quantified using the 2 -∆CT method, as previously described (11).…”
Section: Introductionmentioning
confidence: 99%